The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/vaccines9070778
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Urinary Antibodies and Its Application in Epidemiological Studies for Parasitic Diseases

Abstract: For epidemiological studies of infectious diseases, pathogen-specific antibody levels in an area give us essential and appropriate information. The antibodies against pathogens are usually detected in blood, the drawing of which inconveniences people. Collection of blood increases the risk of accidental infections through blood, and it is difficult to obtain the participation of the target populations, especially the younger generation. On the other hand, urine samples, which contain a high enough level of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…When the effect of the timing of urine collection was studied for Wuchereria bancrofti infection, with urine collections in the early morning and later throughout the day, only a small fluctuation in antibody units was observed and all samples remained positive ( 33 , 34 ). In a urine-based ELISA study conducted for H. pylori , it was observed that the urine water content influenced the concentration of antibody in urine; however, the performance of the qualitative assay on post-fasting urine correlated well with those of serum samples ( 33 , 35 ). Various features of urine, beyond retention time, could influence signal strength relative to serum and deserve future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the effect of the timing of urine collection was studied for Wuchereria bancrofti infection, with urine collections in the early morning and later throughout the day, only a small fluctuation in antibody units was observed and all samples remained positive ( 33 , 34 ). In a urine-based ELISA study conducted for H. pylori , it was observed that the urine water content influenced the concentration of antibody in urine; however, the performance of the qualitative assay on post-fasting urine correlated well with those of serum samples ( 33 , 35 ). Various features of urine, beyond retention time, could influence signal strength relative to serum and deserve future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in urine pH and the presence of microorganisms had no significant effect on the absorbance value of the H. pylori urine-based ELISA. Moreover, sodium azide is commonly added to prevent changes in urine pH resulting from contamination and growth of bacteria ( 33 , 35 ). Patients with significant proteinuria should be tested with caution as demonstrated for the H. pylori urine-based ELISA ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 However, human antibodies shed in urine and feces have not been targeted as a biomarker in wastewater. Fecal antibody levels are correlated with antibody levels in serum 13 , and antibodies have frequently been demonstrated as a potential biomarker for detection of viral 14 and parasitic infections 15 in human urine samples. Antibody measurements from fecal samples have been highlighted as a non-invasive means to rapidly monitor the immune status of wildlife 16 , and similar measurements are increasingly being used for studying various aspects of human health 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, urine-based diagnostic tests involve convenient and completely non-invasive urine sampling, with the limited chance of participants being exposed to biological risks. Previously, urine-based ELISA assays have been suggested as a possible alternative tool to diagnose a number of parasitic helminthiases such as echinococcosis, filariasis, opisthorchiasis, and schistosomiasis ( Itoh et al, 2001 , 2003 ; Sunita et al, 2007 ; Sawangsoda et al, 2012 ; Samad et al, 2013 ; Chirag et al, 2015 ; Eamudomkarn et al, 2018 ; Nagaoka et al, 2021 ; Chungkanchana et al, 2022 ). In this study, we aimed to validate a urine-based SjSAP4 + Sj23-LHD-ELISA assay for the diagnosis of S. japonicum infection in a human cohort recruited from areas in the Philippines moderately endemic for schistosomiasis japonica.…”
Section: Introductionmentioning
confidence: 99%